Theologies of pastoral leadership. Issue 2 (27th May 2020) - Manning, Libby Davis; Nelson, Derek R.
Abstract: The disestablishment of mainline Protestantism as the default religiosity and public theological voice, lamented by many of its members, presents new opportunities for conceiving of pastoral leadership in faithful ways. The pastor as public leader is better imagined as a visionary possibilizer and convener of public conversations, exerting influence in indirectly persuasive ways, rather than as spokesperson for an institution.